A randomized, double-blind, double-dummy, multicenter, controlled trial on brotizolam intervention in outpatients with insomnia. (October 2013) - Yan, Xiaolei; Huang, Shuzhen; Ma, Cui; Shen, Yang; Gu, Niufan; Chen, Haibo; Wu, Wenyuan; Li, Shunwei; Hong, Zhen; Li, Huafang
Abstract Aim. To investigate the efficacy and safety of brotizolam in outpatients with insomnia. Methods. This randomized, double-blind, double-dummy, multicenter, controlled trial recruited 253 outpatients randomized to receive either brotizolam (n = 126) or estazolam (n = 127) for 14 days followed by 1 week of follow-up for rebound detection. Sleep Dysfunction Rating Scale (SDRS) and Clinical General Impression Scale were applied for efficacy evaluation. Safety evaluation was based on data regarding vital signs, physical examination, lab tests, ECG and collection of adverse events. Results. Full Analyses Set (FAS) and Safety Set (SS) included data of 251 subjects, with 126 from brotizolam group and 125 from estazolam group. Per Protocol Set (PPS) analysis included data of 235 subjects, with 121 and 114 from each group. After 14 days of treatment, there was no difference with statistical significance between the two groups regarding SDRS total score change from baseline. FAS and PPS analysis showed that the brotizolam is non-inferior to estazolam in efficacy evaluation. There was also no difference with statistical significance regarding rebound rate between brotizolam and estazolam group in FAS. The rate of adverse event in two groups was with no statistically significant difference in SS. Conclusion. Brotizolam is effective and safe in relieving the symptoms of insomnia.